3D Axisymmetric exact solutions of the piezo-coating sensors for coating/substrate system under charged conical contact. (1st March 2020) - Hou, P.F.; Zhang, W.H.
Abstract: A complete set of frictionless conical contact (indentation) theory of the piezoelectric contact mechanics (PCM) for transversely isotropic piezoelectric elasticity coated system (TIPECS) under charged conical contact is established. 3D exact solutions for the stresses, displacements, electric displacements and electric potential are derived. The contact radius VS the total load relation is obtained, which is valuable to develop the technology of indentation. The relations of coating thickness VS voltage and coating thickness VS voltage are studied. The optimal thickness can be determined with an optimization procedure. Interfacial delamination area of the TIPECS can be predicted with interfacial failure criterion. The theoretical results are helpful for the prediction of some transient electrical effects, which can be combined with experiments to estimate some elastic constants, dielectric constants and piezoelectric constants in the indentation process.